Investigation of Thermal, Microstructure and Shape Memory Behavior of PLA-PEG-PHA Ternary Polymer Blends - Özen, Ecem (My University, 2023)
Instead of blending two polymers to make a blend, a \"ternary polymer blend\" is typically created by adding a third polymer. In recent years, triple polymer blends have found a wide field of study in order to improve and change the properties of traditionally obtained binary blends. In this study, a blend was created by adding Polyhydroxy Alkanoate (PHA) polymer to Polylactic Acid (PLA) and Polyethylene Glycol (PEG) polymers, which are known to be compatible with each other. The aim of this study is to examine the effect of changing PHA amount on the blend of the triple shape memory alloy. The thermal properties, shape memory and scanning electron microscope (SEM) images of this blending were examined. It was investigated which of the samples prepared with three different percentages would give the most ideal results. Although the thermal analysis results are generally close to each other, differences were observed in the shape memory of the material due to the change in the amount. In particular, it can be said that the decrease in the percentage of Polytactic Acid (PLA) polymer, which has binding properties, causes a delay in shape transformation.
Keywords: Polylactic acid; Ternary polymer blends; Shape memory polymers; Polyethlene glycol; Polyhyroxy alkanoate